2019
DOI: 10.5114/fmpcr.2019.90165
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postpartum depression based on women’s quality of life

Abstract: Background. Postpartum depression is the most common problem after childbirth. Objectives. To determine the level postpartum depression, quality of life and predict postpartum depression based on the quality of life of women. Material and methods. This was a descriptive cross-sectional study. The research population consisted of women who were reporting to health care centres in Hamadan, Iran, 2 to 4 weeks after delivery. A total of 300 eligible women were selected using the cluster sampling method. The data g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…And three (7%) studies reported Cronbach’s alpha for the component summary scores: SF-36 [ 58 ] and SF-12 [ 71 , 72 ]. Twelve (28%) studies only reported Cronbach’s alpha for the total scale, even though the instruments do not provide a total scale score: SF-36 [ 57 , 62 64 ], SF-12 [ 65 , 66 , 68 70 , 73 ], and WHOQOL-BREF [ 25 , 74 ]. None of these studies reporting Cronbach’s alpha only for total scales were validation studies.…”
Section: Resultsmentioning
confidence: 99%
“…And three (7%) studies reported Cronbach’s alpha for the component summary scores: SF-36 [ 58 ] and SF-12 [ 71 , 72 ]. Twelve (28%) studies only reported Cronbach’s alpha for the total scale, even though the instruments do not provide a total scale score: SF-36 [ 57 , 62 64 ], SF-12 [ 65 , 66 , 68 70 , 73 ], and WHOQOL-BREF [ 25 , 74 ]. None of these studies reporting Cronbach’s alpha only for total scales were validation studies.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in rural India showed that women who had had a vaginal delivery reported a higher postpartum quality of life (QoL), compared to women who had undergone Cesarean sections [20]. Numerous studies showed that the quality of life, especially with regards to physical health, negatively correlated with the frequency of postpartum depression [21]. However, Wiklund et al conducted a study using the EPDS in 558 women in labor, and observed no significant differences in the occurrence of postpartum depression between women who had had vaginal delivery or Cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Women are more likely to develop PPD if they do not have sufficient social support (Dekel et al, 2017). A further study (Parsa et al, 2019) proves that the high incidence of postpartum mental distress is related to the severity of mental distress, and factors such as poor sleep quality, stress on life's perceptions, and lack of social support.…”
Section: Family Supportmentioning
confidence: 93%